Functional Voice Skills for Music Therapists - Uhlig, Sylka (Voices: A World Forum for Music Therapy, 2019)
This informative book is a guide for the development of functional voice skills for music therapists and students, young clinicians, educators and other health professionals in clinical settings. It presents techniques for emerging a rich, varied, engaging, and healthy clinical voice for use in music therapy practice. The book has a beautiful cover, and invites the reader to take a journey through the uniqueness of the authentic voice. It guides them to discover vocal challenges as well as to find personal vocal strength.